The Dynamics of Vehicles on Roads and Tracks 2016
DOI: 10.1201/b21185-159
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stress prediction in catenary wires for fatigue analysis

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. ABSTRACT: Catenary damping has long been a tuning parameter in pantograph-catenary dynamic interaction models. As the computed contact force is highly sensitive to the choice of damping model or coefficients, it became critical to measure it independently of the pantograph. Original tests have been conducted on a real catenary and damping identification shows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This is used to gain insight on velocity changes associated with reflections and transmissions. Tests detailed in [21] indicate a very low damping close to material properties. Since that is low and constant, no study on damping was performed.…”
Section: Waves Propagating In An Assembly Of Tensioned Wiresmentioning
confidence: 92%
“…This is used to gain insight on velocity changes associated with reflections and transmissions. Tests detailed in [21] indicate a very low damping close to material properties. Since that is low and constant, no study on damping was performed.…”
Section: Waves Propagating In An Assembly Of Tensioned Wiresmentioning
confidence: 92%
“…6,7 A growing number of studies have shown that bending fatigue of contact wire has become a significant issue to be taken into account for OLE safety. 8,9 In existing work the vast majority of studies on fatigue in the contact wire have been experimental. Sugahara et al 10 carried out a number of experiments on fatigue life estimation for overhead contact wire with a servo motor configured to apply oscillating force to contact wire.…”
Section: Introductionmentioning
confidence: 99%